Pendidikan Kecerdasan Spiritual dalam Al-Qur’an Surat Al-Luqman - Yazidul Busthomi; Syamsul A’dlom; Rudy Catur Rohman Kusmayadi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Intelligence is the value of every human being in developing his mindset so that he is able to develop and think clearly to weigh, decide and deal with things by focusing on the problems faced with brilliant solutions. Someone who is intelligent, the conversation he conveys will be structured and has value. When he talks, then what comes out are ideas, ideas, solutions, wisdom, knowledge and dhikr, so that the conversation is always useful. Intelligence is one of the great gifts from God to humans and makes it one of the strengths of humans compared to other creatures. Because with his intelligence, humans can continuously maintain and improve the quality of life that is increasingly complex, through the process of thinking and learning continuously. Spiritual intelligence is the ability to give meaning to worship for every behaviour and activity, through the steps and thoughts that are natural, towards the whole person, and has a monotheistic mindset, and principled "only because of God". Spiritual intelligence education in the Qur'an surah al-luqman is as follows: 1. Prohibition of shirk 2. Trust in God's retribution 3. Commands to prayer 4. Amar ma'ruf and nahi munkar 5. Commands to be patient 6. Prohibition is arrogant 7. Simplify in speaking and lowering voice.